Predictors of willingness to communicate in a second language (L2 WTC): Toward an integrated L2 WTC model from the socio‐psychological perspective - Wei, Xiaobao; Xu, Qingyi (Foreign language annals, 2022)
This study takes the initiative to use structural equation modeling to verify an integrated willingness to communicate in an L2 (L2 WTC) model proposed from the socio‐psychological perspective in the China's English as a second language context. A total of 1007 college freshmen (Male: n = 745; Female: n = 262) from eight universities in mainland China completed six adapted versions of questionnaires concerning L2 learners’ perception of teachers’ emotional support, the ideal L2 self, the ought‐to L2 self, the acculturation to L2 culture, L2 anxiety, and L2 WTC. It was found that the perceived teachers’ emotional support had a direct effect on L2 WTC and an indirect effect through the ideal L2 self, the ought‐to L2 self and the acculturation to L2 culture. It was also found that, although both the ideal L2 self and the ought‐to L2 self were positively related to L2 WTC, the total impact from the ideal L2 self on L2 WTC was much stronger than that of the ought‐to L2 self, with the ideal L2 self contributing more to L2 WTC through the acculturation to L2 culture while the ought‐to L2 self exerting less impact on L2 WTC by arousing higher level of L2 anxiety. Furthermore, this study added to the current literature by showing that the acculturation to L2 culture, which was significantly predicted by the perceived teachers’ emotional support and the L2 ideal self, enhanced the learners’ L2 WTC directly and indirectly by arousing lower level of L2 anxiety. Based on these results, pedagogical significance and implications for further research were suggested. The Challenge Willingness to communicate is a crucial aspect of second language acquisition, and there is considerable evidence that willingness to communicate in an L2 (L2 WTC) is influenced by a variety of psychological, affective, and socio‐cultural factors. However, little is known about how these factors interact with each other in influencing the  L2 WTC. Thus, the focus of this study is to examine the relationships between the students’ perceived teachers’ emotional support and L2 WTC, and the possible mediating roles of the L2 self‐guides and the desire to integrate into L2 culture in between in the China's English as a second language context.